WATER STRESS INDEX IN MAIZE HYBRIDS IN EARLY GROWTH STAGE UNDER WATER VARIATION (International Seven Journal of Multidisciplinary, 2025)
Drought causes morphological changes in corn, especially during the initial phase of its development. This study aimed to evaluate the sensitivity of different maize hybrids to water stress, using the Crop Water Stress Index (IEHC) and infrared thermometer to monitor the water status of plants in the early stages of development. The maize cultivars B2620 PWU, AG8701 PRO 4, P3808 VYHR and DKB360 PRO 3 were tested, submitted to a randomized block design (DBC), in a 4 x 2 x 5 factorial scheme, with 4 replications. The study considered 4 corn hybrids, 2 levels of water replacement (100% and 50% of crop evapotranspiration) and 5 evaluation times (15, 22, 29, 36 and 43 days after emergence - DAE). The lower (LBL) and upper (UBL) baselines for the IEHC calculation were determined by the lowest and highest air temperatures recorded throughout the crop cycle. The data were submitted to analysis of variance and, when significant, the qualitative data were analyzed by Tukey's test at p